Pengaruh Gaya Kepemimpinan Transformasional Dan Lingkungan Kerja Terhadap Kepuasan Kerja Di PT Nizar Pratama Jaya - Mohamad Ikbal; Asep Suherman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the influence of transformational leadership style and work environment on job satisfaction at PT Nizar Pratama Jaya, both partially and simultaneously. This research uses a quantitative method with an associative approach. The total population and sample size is 82 employes from PT Nizar Pratama Jaya. The data analysis techniques used are validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient, determination coefficient, and hypothesis testing. With the results showing that Transformational Leadership Style has a positive and significant effect on Job Satisfaction with the regression equation Y = 23.089 + 0.487X1, the hypothesis test obtained a t-statistic value > t-table or (6.965 > 1.664) and a significance value < 0.05 or (0.000 < 0.05). Therefore, H0 is rejected and H1 is accepted. The Work Environment has a positive and significant effect on Job Satisfaction with the regression equation Y = 27.157 + 0.377X2. The hypothesis test obtained a t-statistic value > t-table or (3.904 > 1.664) with a significance value < 0.05 or (0.000 < 0.05). Therefore, H0 is rejected and H2 is accepted. Transformational Leadership Style and Work Environment simultaneously have a positive and significant effect on Job Satisfaction with the regression equation Y = 19.350 + 0.432X1 + 0.143X2. The hypothesis test obtained a value of F-statistic > F-table or (25.852 > 3.11), followed by a significance value of 0.000 < Based on the results above, the recommendation is to provide inspirational motivation and improve the room's lighting and ventilation systems, which can effectively increase Job Satisfaction at PT Nizar Pratama Jaya..